TRENDS OF SHAPING ARCHITECTURE OF ECOLOGICAL TREATMENT AND REHABILITATION COMPLEXES - Zaporozhchenko, Oksana; Dugina, Vera (Proceedings of National Aviation University (archive), 2014)
The trends of shaping architecture of environmental rehabilitation complexes associated with environmental design principles and specific requirements of this type of building structures were considered